Patient safety goals training at Charlie Hospital - Niken Sukesi; Nana Rohana (Universitas Muhammadiyah Magelang, 2022)
Patient safety has become a very important, even global issue. Various cases of accidents that occurred in various health institutions have become a case that worries many parties. Especially for leadership in units in health service institutions such as health centers, health clinics, and hospitals. Characteristics of a hospital that contains 4 types of complete risk factors (biological, ergonomic, chemical, and physical factors) are not easy to control, especially without a system control program. The purpose of this service is to increase knowledge and change the behavior of nurses in implementing patient safety goals. Which method is used in the form of training and mentoring to assess change in nurse behavior? The results of this service after being given a pre and post-test test there is an increase in the knowledge of nurses before and after education regarding patient safety.